Self-determined First Nations museums and colonial contestation : the keeping place. - Hudson, Robert, 1955-; Woodcock, Shannon (Abingdon, Oxon ; New York, NY : Routledge, 2022)
Self-Determined First Nations Museums and Colonial Contestation explores Indigenous practices of curation, object repatriation, and cross-cultural community engagement in a dynamic Koori museum. Grounded in the fact that Gunai Kurnai people have never ceded sovereignty, the text reorients dominant temporal and colonial approaches of museum studies to document and theorise Gunai Kurnai self-presentation and community engagement in the Krowathunkooloong Keeping Place. Researched and co-authored by the Cultural Manager of the Keeping Place, Gunai Kurnai Monero Ngarigo man Robert Hudson, and white Historian Shannon Woodcock, the book traces the temporal, social, and cultural considerations of the Elders who curated the permanent exhibition in the early 1990s. Discussing community management of a collection growing through the ongoing repatriation of tools, art, and Ancestor remains, the text also explores how Robert Hudson engages with visitors to the Keeping Place and local colonial history museums, and theorises the power of Gunai Kurnai work with individuals and institutions in the small museum context. Finally, Hudson and Woodcock demonstrate that the Keeping Place articulates sophisticated Gunai Kurnai-grounded methodologies of museum practice in relation to international critical Indigenous studies scholarship. Self-Determined First Nations Museums and Colonial Contestation provides a vital case study of an Indigenous museum space written from an inside perspective. As such, the book will be essential reading for scholars and students engaged in the study of museums and heritage, Indigenous peoples, decolonisation, race, anthropology, culture, and history.
OCLC-licensed vendor bibliographic record.
Keywords: Museums and indigenous peoples; Koori (Australian people) -- Museums; Koori (Australian people) -- History; SOCIAL SCIENCE -- Anthropology -- Cultural; SOCIAL SCIENCE / Anthropology / Cultural